ANALISIS MEDIA PEMBELAJARAN IPAS PADA MATERI LISTRIK STATIS DAN DINAMIS BAGI SISWA SEKOLAH DASAR - Eka Farwati; Novita Sari; Nurul Hasanah (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to explore the forms and effectiveness of the use of learning media on static and dynamic electricity in Natural and Social Sciences (IPAS) learning at the Elementary School level. The background of this study is based on students' difficulties in understanding abstract electricity concepts and teachers' limitations in utilizing technology-based media. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation in several Elementary Schools that have implemented learning media in IPAS. The results of the study indicate that learning media, both conventional and digital, play an important role in increasing student engagement, conceptual understanding, and learning motivation. Digital media such as animated videos and interactive simulations (PhET) have been proven to be able to explain abstract phenomena visually and concretely, while simple teaching aids such as electroscopes are effective in demonstrating static electricity phenomena. The obstacles faced include limited technological infrastructure and teacher competence in using digital media. Therefore, teacher training and the provision of supporting facilities are key to optimizing media-based learning. This study recommends the use of interactive media as a contextual, engaging, and appropriate IPAS learning strategy that is appropriate to the cognitive characteristics of Elementary School students.